Regular pattern mining on multidimensional databases - Sreedevi, M; Harika, V; Anilkumar, N; Sai Thriveni, G (International Journal of Engineering and Technology, 2018)
Extracting general patterns from a multidimensional database is a tricky task. Designing an algorithm to seek the frequency or no. of occurring patterns and really first-class transaction dimension of a mining pattern, general patterns from a multidimensional database is the objective of the task. Analysis prior to mining required patterns from database hence, Apriori algorithm is used. After the acquiring patterns, they have been improved to many further patterns. Nevertheless, to mine the required patterns from a multidimensional database we use FP development algorithm. Here, now we have carried out a pop-growth procedure to mine fashionable patterns from multidimensional database established on their repute values. Utilizing this opportunity, we studied about recognizing patterns which give the reputation of every object or movements inside the entire database. Whereas Apriori and FP-growth algorithm is determined by the aid or frequency measure of an object set. As a result, to acquire required patterns utilizing these programs one has to mine FP-growth tree recursively which involves extra time consumption. We have utilized a mining process, which is meant for multidimensional recognized patterns. It overcomes the limitations of present mining ways by implementing lazy pruning method followed by showing downward closure property.Â Â